The Influence of Debt to Equity Ratio, Company Size and Current Ratio on Profit Growth with Return on Assets as an Intervening Variable in Property and Real Estate Sub-Sector Companies Listed on the Indonesian Stock Exchange Period - Yusnia Widiastuti; Joko Utomo; Kertati Sumekar (Journal of Finance and Business Digital, 2023)
This research examines the effect of debt to equity ratio, company size and current ratio on profit growth with return on assets as an intervening variable in property and real estate sub-sector companies listed on the Indonesia Stock Exchange for the 2018-2022 period. The research sample was 25 companies. The data type is quantitative data. This data source uses secondary data. Data collection uses documentation techniques. The data analysis used is Structural Equation Modeling. Based on the results of the analysis, it shows that the debt to equity ratio has a negative and significant effect on return on assets, company size has no effect on return on assets, the current ratio has no effect on return on assets, the debt to equity ratio has no effect on profit growth, company size has no effect. on profit growth, the current ratio has a negative and significant effect on profit growth, return on assets has a positive and significant effect on profit growth